Adaptation mechanism of root morphology and chemical traits in herbaceous plants on the jingpo lake lava platform, China (Bangladesh Journal of Botany, 2026)
Present study was conducted explore the functional traits of herbaceous root systems with varying life-histories adaptive strategies on Jingpo Lake lava platform. Seventeen dominant herbaceous species from the lava platform of Jingpo Lake was selected to determine the morphological and chemical traits of roots at different branching orders, and explored their resource acquisition strategies. Values varied between 0.11-75.47% for annuals and 13.57-94.81% for perennials with different life-histories plants. The smallest variation occurred in RCC, while the largest variation was observed in SRL. The SRL, RD, and RTD between two life-histories showed significant differences (P < 0.05). Correlations between root traits differed across plant life-histories and root sequences. Annual plants tend to favor an “acquisition” strategy, characterized by rapid “foraging”, whereas perennial plants adopt a more “conservative” strategy with slower “foraging”. Redundancy analysis indicated that soil pH accounted for the largest contribution (54.7%), followed by SANC (23.4%).Bangladesh J. Bot. 55(1): 181-190, 2026 (March)